1990
DOI: 10.1007/bf01015751
|View full text |Cite
|
Sign up to set email alerts
|

Minimal treatments and problem gamblers: A preliminary investigation

Abstract: In view of the increasing popularity of minimal intervention treatments for problem drinking, a self-help manual for people who wish to reduce or stop gambling was prepared. Twenty-nine (ACT residents) who responded to advertisements for help with problem gambling were allocated to either of two minimal treatments, "Manual (only)" and "Manual & Interview". On average, clients from both groups reduced the frequency of their gambling sessions, frequency of overspending, and amount spent per week in the first thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 15 publications
0
34
0
2
Order By: Relevance
“…One study of a brief intervention in the form of a workbook (which included cognitivebehavioral and motivational enhancement techniques) was compared with the use of the workbook plus one clinician interview [38]. Both groups reported significant reductions in gambling at a 6-month follow-up.…”
Section: Treatment Of Pathological Gamblingmentioning
confidence: 99%
“…One study of a brief intervention in the form of a workbook (which included cognitivebehavioral and motivational enhancement techniques) was compared with the use of the workbook plus one clinician interview [38]. Both groups reported significant reductions in gambling at a 6-month follow-up.…”
Section: Treatment Of Pathological Gamblingmentioning
confidence: 99%
“…Dickerson and others evaluated a minimal intervention for gamblers by comparing a self-help manual mailed to subjects with the manual plus telephone and postal contact only (69). The manual-only group reduced their weekly gambling sessions and weekly dollars wagered for the 6 months following the manual's mailing, whereas the manual-plus-interview group showed this reduction for only 3 months postinterview.…”
Section: Cognitive-behaviourally Oriented Treatment Studiesmentioning
confidence: 99%
“…Research suggests that moderate or mild problem gamblers are able to employ practical, problem-focused strategies and that such gamblers might benefit from the development of easily accessible intervention (Toneatto et al, 2008). Although the mechanisms for change remain unknown, extant research has demonstrated the benefits of self-help options (Dickerson, Hinchy, & England, 1990;Hodgins, Currie, & el-Guebaly, 2001). …”
Section: Treatments For Problem Gamblingmentioning
confidence: 99%